Semangat Pluralisme Untuk Menjaga Keutuhan NKRI - Fatakhul Huda (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2020)
The Indonesian nation was created by Allah SWT as a plural nation based on ethnicity, culture, race and religion by having the motto of Unity in Diversity. Plurality is a sociological reality which in reality society is indeed plural. Plural basically shows more than one and ism is something related to understanding or flow. Thus pluralism is an understanding or attitude towards multiple or many circumstances in everything including social, cultural, political and religious All religions also strengthen national integration through teachings that emphasize a sense of fairness, compassion, tolerance of religious harmony, unity, unity, brotherhood and togetherness. Besides that, the noble values ​​of culture and maintaining the integrity of the Unity and Unity of the Indonesian nation which is manifested through customs also play a role in binding the inner relations within each citizen and Indonesian nation. And if all that is not realized then there will be many conflicts in Indonesia. The young generation must possess and instill a high sense of pluralism in providing a tolerance of religious harmony in Indonesia. Leaders are born from young generations to succeed the ideals of the Indonesian people. Along with this pluralism, especially in Indonesia, there is an importance if we understand that in fact, all the differences that we have are not basic, not the breath of the establishment of the Unitary Republic of Indonesia. However, the Homeland was formed because of similarities and not differences.